Pertanggung Jawaban Direksi Terhadap Pemindahan Hak Atas Saham Aset Tanpa Melalui Rups - Intan Nurul Arifin; Mahrus Sholeh; Sumriyah Sumriyah (Lembaga Pengembangan Kinerja Dosen, 2023)
Ownership of company shares entitles shareholders to do a number of things, such as attending and voting at GMS, receiving dividend payments and liquidation results; as well as. other rights pathways according to law. So that the ownership of the rights to shares is important to be able to have these rights, of course there must be proof of ownership of the rights to these shares. And if at any time the shares owned want to be sold or or transferred to the hands, a deed of transfer of rights over shares is required to be carried out with a deed of transfer rights. The deed of transfer of rights can be made in the form of a notarized deed or private deed. The deed of transfer of rights or compensation is submitted in writing to the Company. Which then records the transfer by the director.